Cigarette Smoke and Cancer Health Among Incarcerated Men in U.S. Northeastern Prison Facilities. (July 2019) - Valera, Pamela
Incarcerated men, an understudied population, have not been the focus of cancer prevention studies. The Cancer Risk in Incarcerated Men Study was developed to examine smoking behaviors and cancer health among 236 incarcerated men. The participants were between 19 and 86 years of age. Only 30.5% of the sample reported receiving a cancer screening test and less than 5% reported being diagnosed with cancer. In terms of the cancer screening test provided, 43.6% reported having had a prostate-specific antigen test, 19.2% a fecal occult blood test, and 11.4% a sigmoidoscopy or a colonoscopy. Age was the only significant predictor of having a cancer screening procedure ( B = .10, p < .001). This study demonstrates the need to promote cancer prevention studies among incarcerated populations.